2014
DOI: 10.1186/1471-2334-14-5
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis mortality: patient characteristics and causes

Abstract: BackgroundIn the antibiotic era, tuberculosis (TB) still causes a substantial number of mortalities. We aimed to identify the causes and risks of death among TB patients.MethodsMedical records of mortality cases of culture-proven TB diagnosed during 2003–2007 were reviewed. All TB deaths were classified into 2 groups (TB-related and non-TB-related), based on the underlying cause of death.ResultsDuring the study period, 2016 cases (male: 71.1%) of culture-proven TB were identified. The mean age was 59.3 (range:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
77
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(109 citation statements)
references
References 24 publications
14
77
1
2
Order By: Relevance
“…Our study also confirmed the findings of previous studies that delayed initiation of anti-tuberculosis agents was an independent factor of respiratory failure and worse clinical outcomes (5,19,20,32). Therefore, patients suspected of acute tuberculous pneumonia need to be considered for development of acute respiratory failure and antituberculosis agents must not be delayed in such patients.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Our study also confirmed the findings of previous studies that delayed initiation of anti-tuberculosis agents was an independent factor of respiratory failure and worse clinical outcomes (5,19,20,32). Therefore, patients suspected of acute tuberculous pneumonia need to be considered for development of acute respiratory failure and antituberculosis agents must not be delayed in such patients.…”
Section: Discussionsupporting
confidence: 82%
“…Half of the patients required mechanical ventilator support. The overall mortality rate was 30.2% which is comparable to previous reports (5,(19)(20)(21). We found that shorter duration of illness, underlying disease of AIDS, development of fever and dyspnea on presentation, large amount of acid fast bacilli on sputum smear, lower serum albumin level, and delayed initiation of anti-tuberculosis agents were among the independent risk factors to develop acute respiratory failure requiring mechanical ventilator support.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…An epidemiological study of Yang et al showed the tuberculosis incidence and related burden was decreased in wenchuan earthquake-stricken area from 2004-2012 [24]. Lin et al in a study on TB mortal cases showed that patients with inappropriate organ function were in the risk of septicemia and fatality [25]. The Human Immunodeficiency Virus infection is another [26] related risk factor.…”
Section: Discussionmentioning
confidence: 99%